Effects of Rice Bran, Flax Seed, and Sunflower Seed on Growth Performance, Carcass Characteristics, Fatty Acid Composition, Free Amino Acid and Peptide Contents, and Sensory Evaluations of Native Korean Cattle (Hanwoo) - Chang Bon Choi; Hana Kwon; Sung Il Kim; Un Mok Yang; Ju Hwan Lee; Eun Kyu Park (Asian-Australasian Journal of Animal Sciences, 2016)
This study was conducted to evaluate the effect of dietary supplementation with rice bran, flax seed, or sunflower seed to finishing native Korean cattle (Hanwoo) on growth performances, carcass characteristics, fatty acid composition, free amino acid and peptide contents, and sensory evaluations of Longissimus muscle (LM). A total of 39 Hanwoo steers (average age of 22.2 mo and average body weight (BW) of 552.2 kg) were randomly divided into Control, rice bran (RB), flax seed (FS), or Sunflower seed (SS) groups. The steers were group fed for 273 d until they reached an average age of 31.2 mo. Final BW was 768.2, 785.8, 786.2, and 789.0 kg, and average daily gain was 0.79, 0.85, 0.82, and 0.84 kg for the Control, RS, FS, and SS groups, respectively (p>0.05). Fat thickness of the FS group (19.8 mm) was greater (p<0.05) than that of the other groups. Final yield grade converted into numerical values was 2.0 for the RB group, 1.7 for the Control and SS groups, and 1.4 for the FS group. Marbling degrees for the Control, SS, RB, and FS groups were 5.3, 5.1, 4.7, and 4.6, respectively. Percentages of palmitic acid (C16:0), stearic acid (C18:0), and arachidic acid (C20:0) in the LM were not different among the groups. Palmitoleic (C16:1) acid was higher (p<0.05) in the SS group. The concentration of oleic acid was highest (p<0.05) in the Control group (47.73%). The level of linolenic acid (C18:3) was 2.3 times higher (p<0.05) in the FS group compared to the other groups. Methionine concentration was (p<0.05) higher in FS (1.7 mg/100 g) and SS (1.2 mg/100 g) steers than in the Control or RB groups. Glutamic acid and α-aminoadipic acid (α-AAA) contents were (p<0.05) higher in the FS group compared to the other groups. LM from the FS group had numerically higher (p>0.05) scores for flavor, umami, and overall palatability in sensory evaluations. In conclusion, supplementation of flax seed to diets of finishing Hanwoo steers improved sensory evaluations which might have been caused by increases in flavor related amino acids such as methionine, glutamic acid and α-AAA and peptides, anserine and carnosine, and their complex reactions.